Enhancing Students' Earthquake and Tsunami Preparedness Through Comic Media Health Education: A Quasi-Experimental Study - Rahayu, Putri Puji; Syaharani, Ghifara Alita; Setioputro, Baskoro; Yunanto, Rismawan Adi; Haristiani, Ruris (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Background: Indonesia is located in the Ring of Fire area at the meeting point between the Eurasian Plate, the Indonesia-Australian Plate, and the Pacific Plate. This meeting was the source of the megathrust earthquake in the East Java region. This makes Indonesia vulnerable to earthquakes and tsunamis along the southern coast of Java. As a vulnerable group to facing potential earthquakes and tsunamis, the level of preparedness of children in Indonesia needs to be increased. Aim: To determine the effect of comic media health education on the Earthquake and Tsunami Preparedness level of students at SDN Sumberejo 09 Ambulu Jember. Method: The sample of this study was students in SDN Sumberejo 09 Ambulu Jember. The research design used a quasi-experiment using the non-equivalent control group design and probability sampling with the proportionate stratified random sampling approach. Data collection used a characteristic questionnaire and an earthquake and tsunami preparedness questionnaire by LIPI-UNESCO 2006. Result: The result of the study shows differences in the level of preparedness before and after the intervention in the intervention group with a p-value of 0.000 (<0.05). At the same time, there was no difference in preparedness between the data before and after in the control group, with a p-value of 0.101 (>0.005). Conclusion: Comic media has been proven to increase elementary school students’ preparedness.